Adolescent substance use in Costa Rica: findings from a national survey among secondary school students - Montero-Zamora, Pablo; Lopez-Soto, Andrea; Cordoba, Jeancarlo; Ramirez, Esmeralda (Frontiers in Public Health, 2025)
BackgroundAdolescent substance use (alcohol, tobacco, e-cigarette, marijuana, and other illegal drug use) is a growing public health concern in Latin America. In Central America, Costa Rica consistently reports among the greatest rates of alcohol and marijuana use among secondary school students in the region. However, nationally representative, peer-reviewed studies examining prevalence and etiologic factors remain scarce. This study aimed to examine the prevalence, distribution and associated etiological factors of substance use among Costa Rican adolescents.MethodsWe analyzed data from the 2021 VI National Survey on Psychoactive Substance Use in the Secondary School Population, a cross-sectional, nationally representative survey of 3,524 students (weighted N ≈ 354,330) aged 11–20 years. We described the lifetime prevalence of alcohol, tobacco, e-cigarette, marijuana, and other illegal drug use and examined associations with sociodemographic, familial, and emotional distress variables using multivariate logistic regression.ResultsAlcohol was the most commonly used substance (55.9%), followed by e-cigarettes (13.3%), tobacco (9.8%), other illegal drugs (7.4%), and marijuana (7.2%). Substance use was associated with older age, higher weekly allowance, working while studying, and family substance use. Emotional distress indicators—loneliness, sadness, and suicidal thoughts—were significantly associated with alcohol, tobacco, and other illegal drug use. Parental school monitoring was protective against alcohol use. Notably, e-cigarette use was inversely associated with suicidal thoughts and family smoking.ConclusionThis is the first peer-reviewed study to report nationally representative estimates of adolescent substance use in Costa Rica. Findings underscore the multifactorial etiology of substance use and highlight the need for culturally tailored, evidence-based prevention interventions in Costa Rica and Central America.